(untitled) (Research, Society and Development, 2022)
Introduction: Several physical, spiritual, biological, social and psychological limitations become very specific when dealing with patients not only in a terminal condition, but throughout the course of diseases no longer treatable by therapeutic resources. Palliative Care (PC) is a specific way of caring, where the team plays a fundamental role in pain relief, since scientific resources are no longer useful to stop the disease from progressing. Objective: To present, through the literature, the holistic humanization of cancer patients in palliative care. Methodology: This is an integrative literature review, with a qualitative approach and exploratory in nature, 8 articles indexed and published in the MEDLINE, LILACS and BDENF databases were used for this review. Results and Discussion: Cancer patients face several biopsychosocial challenges, especially in patients with advanced stages of the disease, when this occurs, these patients are said to be in PC. According to the results obtained, the importance of multidisciplinary participation in these care is noted, where actions will mainly be developed that will alleviate pain and suffering, providing a quality of life. Final Considerations: Palliative care is possible when there is an active multidisciplinary action that includes the patient, their families and the health team, aiming to provide the best care to the patient, adapting to their situation and biological, physical and social needs. The participation of the team in PC is, therefore, of total importance to provide holistic humanization and relief from incurable diseases.